Determinación espacial de la distribución de la Eichornia crassipes “Jacinto de agua” en las fuentes de agua Lóticas ubicadas en la margen derecha del Río Mayo - Lozano Lozano, Cinthya (2010)
The right margin of the river In May presents permanent tributaries, inside which one finds the Rio Negro, Rosemary and Tioyacu, rivers that there were identified and prioritized for the present study, the same ones that possess own and similar characteristics for a correct application of the statistical used design. Floating studied species Eichornia crassipes 11 Water hyacinth 11 , he presents plunged roots, lacks apparent stem, provided with a rhizome, very particular! y, emergent, of that there is opened a rosette of leaves that have a spongy surface notably inflated in the shape of globe that forms a bladder full of air, by means of which the vegetable can be kept on the aquatic surface and high reproductive capacity in water bodies lenticos principally. For. the present evaluation one raised as hypothesis that the species Eichornia crassipes "Water hyacinth 11 , it is distributed in the rivers Rosemary, Black and Tioyacu. His observation in field was orientated by means of such aims as to determine the spatial distribution in the rivers before mentioned across the zoning of the principal sources of water, determination of the percentage of the spatial distribution and identification of the biometric characteristics ofthe species in study. Since there decided result that the Spatial Distribution of the Eichornia crassipes 11 Water hyacinth 11 , in the Rivers Rosemary, Black and Tioyacu, they are to a height between the 822 and 840 m.s.n.m., in case of the Río Negro we find it in the coordinates UTM: X 249611, And 9332666 (Point N°16) to 2000 meters of the Cement bridge of the road carrozable that Leads us to San Vicente's hamlet; in the river Rosemary we find it in the coordinates UTM: X 249880, Y9332679 (Point N°05) at a height of the center filled with Tamboyacu and in the Río Tioyacu we find it in the coordinates UTM: X 146541, And 9338263 (Point N°02) at a height of the bridge of I make concrete that he leads to the Playtime His Ecoturístico Tioyacu. The spatial distribution of the Eichornia crassipes 11 Water hyacinth " Fernando Belaunde Terry comes to 100% ofthe surface ofthe mirror ofthe water ata height ofthe road (Point of Reference like Artificial Corridor), the above mentioned percentage is kept constant up to the Rio In May. His presence is related in addition to the decrease of the height, speed and increase of the temperature and especially in surfaces to presence of established populations. The externa} physical conditions (T °C, Altitude ), chemistries (pH), between other properties influence determinantemente the spatial distribution of Eichornia crassipes 11 Water hyacinth 11 , the species needs from low speeds of the water, minor altitudes, T o nearby between 20 and 23°C, and amorphous bodies of water; the zone in study presents populations who in the main on not having possessed systems of sewers do that the served waters, solid and sanitary residues are derived to the water sources across the superficial run-offproduct ofthe rain rainfalls principally; On the other hand in the zone the culture of rice predominates to technical irrigation what makes suppose the insertion of high percentages of nitrogenous, phosphoreted and sulfation products, principal components for his ideal development and permanency in the water bodies. All this comes generating the deterioration of the aquatic ecosystems, because of the covering of the surface of the mirror of the water, it diminishes the light efficiency in the aquatic so urce, when prevents the step of the solar beams, which carries to the reduction of the content of oxygen and productivity. The presence of fitofaga fauna and carnivorous in these water plants it presupposes the proliferation of infectious vectors and the loss of the navigability of the water bodies for the high population densities of Eichomia crassipes " Water hyacinth "they impede the efficient use as route oftransport. Key words: physical conditions, rivers.